Strategies to Increase The Competence and Professionalism of Vocational High School Teachers - Rita Aryani; Elsah Fanisyah (Edumaspul: Jurnal Pendidikan, 2023)
Competent and professional teachers are the key to success in realizing vocational graduates who are ready to work. The purpose of this study is to determine strategies to increase the competence and professionalism of vocational teachers. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. In the results of the research, it is known that strategies are used to improve teacher competence and professionalism through stages planning stages carried out to identify and adjust the needs or findings of problems sought for joint solutions. The next stage is the implementation of the determination of competency and professionalism improvement activities made at the planning stage. This research is expected to be a strategy for vocational teachers and vocational schools to improve their teachers' competence and professionalism.